Expression, Purification, and Preliminary Protection Study of Dehydrin PicW1 From the Biomass of Picea wilsonii - Liu, Junhua; Dai, Mei; Li, Jiangtao; Zhang, Yitong; Ren, Yangjie; Xu, Jichen; Gao, Wei; Guo, Sujuan (Frontiers in Bioengineering and Biotechnology, 2022)
Dehydrins (DHNs) belong to group Ⅱ of late embryogenesis abundant (LEA) proteins, which are up-regulated in most plants during cold, drought, heat, or salinity stress. Despite the importance of dehydrin for the plants to resist abiotic stresses, it is necessary to obtain the plant derived dehydrin from different biomass. Generally, dehydrin PicW1 from Picea wilsonii involved in Kn type dehydrin with five K-segments, which has a variety of biological activities. In this work, Picea wilsonii dehydrin PicW1 was expressed in Escherichia coli and purified by chitin-affinity chromatography and size exclusion chromatography, which showed as a single band by SDS-PAGE. A cold sensitive enzyme of Lactate dehydrogenase (LDH) is used to explore the protective activities of other proteins. Temperature stress assays showed that PicW1 had an effective protective effect on LDH activity, which was better than that of Bovine Serum Albumin (BSA). This study provides insights into the purification and protective activity of K5 DHNs for advancing on dehydrin structure and function from biomass.